Finite element simulation and experimental analysis of orthogonal cutting of an aluminium alloy using Polycrystalline Diamond tools. (2nd December 2009) - Davim, J. Paulo; Reis, P.; Maranhao, C.; Jackson, M.J.; Cabral, G.; Gracio, J.
The current paper presents a Finite Element Model (FEM) simulation and experimental analysis of orthogonal cutting on aluminium alloy using Polycrystalline Diamond (PCD) tools. FEM machining simulations used a Lagrangian finite element-based machining model, AdvantedgeTM, applied to predict cutting forces, temperature distribution, plastic strain, von Mises and maximum shear stresses. The orthogonal cutting model was validated by comparing cutting forces obtained experimentally with a thermo-mechanical FEM analysis under orthogonal cutting conditions. Finally, FEM analysis prediction of the evolution of plastic strain, von Mises stress and maximum shear stresses during the machining of a commonly used aluminium alloy using PCD tools was conducted.